VAT Refunds : A Review of Country Experience - Harrison, Graham; Krelove, Russell (Washington, D.C. : International Monetary Fund, 2005)
A key feature of the invoice-credit form of value-added tax (VAT) is that some businesses- notably exporters-will pay more tax on their purchases than is due on their sales, and so can seek refunds of excess credits from government. While refunding is straightforward in principle, serious problems arise in practice, including opportunities for fraud and corruption, and denial of refunds by governments with cash shortages. This makes the refund process the "Achilles heel" of the VAT. This paper examines the refund approaches of tax administrations in 36 developing, transitional, and developed countries. It evaluates the effectiveness of these approaches and suggests a model of best practice that takes into consideration compliance issues faced by countries during different stages of development.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet